Elder abuse and nursing: what nurses need to know and can do about it - Miller, Carol A. (Springer Publishing Company, 2017)
Introduction to elder abuse for nurses : forms, settings, risks, and consequences -- Elder abuse in domestic settings by a trusted other -- Elder abuse in domestic settings : self-neglect -- Elder abuse in long-term care facilities -- Cultural considerations related to elder abuse -- Laws related to elder abuse and roles of nurses as reporters -- Tools and guides for nurses to detect elder abuse -- Ethical issues related to elder abuse for nurses -- Unique aspects of nursing assessment related to elder abuse -- Unique aspects of nursing interventions related to elder abuse -- Resources for addressing elder abuse -- Nurses in action addressing domestic elder abuse across settings -- A nurse in action caring for a self-neglecting older adult -- A nurse as a member of a multidisciplinary team preventing elder abuse -- Financial abuse of older adults in its many forms and guises -- Sexual abuse of older adults in its many forms and guises